Disenfranchised grief: the emotional impact experienced by foster carers on the cessation of a placement. (March 2019) - Lynes, David; Sitoe, Angela
This study uses a qualitative approach to explore the experiences of 22 UK foster carers when a child is 'moved on' from a placement, focusing specifically on their experiences of loss. In most cases participants report loving the child as their own and describe their surprise at the profundity of their feelings of loss and grief when living through the child's departure. These emotions can be fruitfully perceived as 'disenfranchised grief' in that its severity was unexpected and was not recognised as legitimate by the carers' social group or professionals working with them. As a result, their loss was neither perceived as legitimate nor given a vehicle for expression. In some cases, participants report that the experience changed their approach to caring for children and even resulted in them ceasing to foster. The implications for practice include preparing foster carers to expect a grief response when their children move on, to recognise that this might be disenfranchised and to enhance peer and professional support during that process.